Textbook Policy of Vietnam: Critical Study and a Way-Forward towards Transformation - Thanh, Tam Nguyen; Minh, Duc Nguyen; Do, Thu Ha; Thi, Huyen Cao; Nguyen, Thi Thu Hang (Journal of Posthumanism, 2025)
The implementation of the new 2018 general education curriculum in Vietnam has led to a significant transformation in the country's school textbook policy, shifting from a single nationally unified set of textbooks to a "one curriculum - many textbooks" model. This change reflects a positive shift in the mindset of educational managers in Vietnam, aiming to improve the educational system and promote critical thinking and problem-solving skills among children. The study employed a qualitative approach, utilizing interviews as the primary data collection method. The interviews were conducted until theoretical saturation was achieved, ensuring that the data collected was comprehensive and representative of the research topic. No preregistration numbers or animal species were involved in this study. The findings of the study highlight the challenges associated with transitioning from a centralized, exclusive model to a decentralized approach in textbook publishing. Despite these challenges, the "one curriculum - many textbooks" model has the potential to promote inclusiveness and diversity in educational and training systems. In conclusion, the introduction of the "one curriculum - many textbooks" model in Vietnam's educational system is a step towards promoting critical thinking, problem-solving skills, and effective management of educational budgets. The study suggests that this policy has the potential to improve the overall quality of education in Vietnam, and its implementation should be carefully monitored and evaluated to ensure its effectiveness in achieving the desired outcomes.